Migration intentions and associated factors among early career doctors at Jaffna Teaching Hospital - Sasika Nipun, S.A.; Saliha, N.; Laksha, T.; Fathima Misfera, M.S.; Ravishka Dulaj, P.; Kumar, R.; Venoden, D. (University of Jaffna, 2024)
Background: Since the 1970s, brain drain to the West has been a major problem in Sri Lanka that intensified in the Northern Province as a result of the civil war. The current economic crisis is pushing more and more doctors to migrate abroad. This study aims to determine the proportion of early career doctors (preliminary grade and grade II medical officers, including registrars) at Teaching Hospital Jaffna who intend to migrate abroad, the factors associated with their migration intentions and their reasons for wanting to migrate abroad. Methods: This hospital-based descriptive cross-sectional study was conducted among all early career doctors (preliminary grade and grade II medical officers, including registrars) working at Teaching Hospital Jaffna. Data were collected from all doctors matching the study criteria through a self-administered questionnaire. Data were analysed using SPSS (v27). Standard descriptive statistics and the chi square test were used in the analysis (critical level 0.05). Results: In total, 148 doctors participated (response rate 54.2%). Two-thirds were in the 25-35 years age group (66.9%), just over half were females (50.7%), and the majority were of Tamil ethnicity (93.2%) with permanent residence in Jaffna district (79.1%). In total, 57 (38.5%) early career doctors intended to migrate (38.5%). Younger age (p= 0.013), not having postgraduate qualifications (p=0.018), wanting to pursue postgraduate studies (p=0.048) and having experience abroad (p=0.010) were significantly associated with the intention to migrate. Key push factors were economic instability (strongly agree 82.5%, agree 12.3%), political instability (strongly agree 78.9%, agree 12.3%), corruption (strongly agree 64.9%, agree 19.3%) and insufficient income (strongly agree 45.6%, agree 31.6%). Common pull factors included better future for children (strongly agree 54.4%, agree 38.6%), better living standards (strongly agree 66.7%, agree 24.6%), stable future (strongly agree 61.4%, agree 33.3%), and stable political and economic situation (strongly agree 57.9%, agree 35.1%). Conclusions: Over a third of early career doctors at Teaching Hospital Jaffna have intentions to migrate abroad with younger doctors more likely to express such intentions. Key reasons for migration relate to economic and political instability in Sri Lanka. The government needs to take urgent steps to address the economic and health crises to ensure access to quality healthcare for the people of Sri Lanka.
Keywords: Health brain drain; Medical professionals; Health systems; Migration; Sri Lanka